Analisis keterkaitannpertumbuhan ekonomi dan kemiskinan terhadap kualitas lingkungan hidup di pulau sumatera dengan pendekatan data panel dan granger causality test - Aminah, Aminah; Ridwansyah , M.; Hari Prihanto, Purwaka (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2024)
The purpose of this study knowing the influence and reciprocal relationship of economic growth, poverty on the environmental quality index. The data used are secondary data obtained from the Environmental Agency and the Central Statistics Agency. The results of multiple linear regression analysis with panel data Economic Growth Variables have no effect and are not significant, while the Poverty Variable has a positive and significant effect on IKLH .While for the Granger Causality the results show that the interaction between IKLH on Economic Growth that has a reciprocal relationship  is the Province of North Sumatra, West Sumatra and Bengkulu. And the interaction between IKLH on Poverty does not have a reciprocal relationship in 10 Provinces on the Island of Sumatra